A SYSTEMATIC REVIEW OF WEB 2.0 TECHNOLOGIES IN LIBRARY WEBSITES (2010 – 2023) - Barman, Dhiru; Das, Dhrubajit (International Journal of Research -GRANTHAALAYAH, 2025)
Web 2.0 technologies have reshaped library services by facilitating participatory engagement, user-centered design, and real-time integration. Despite widespread implementation, their impact remains uneven across geographic and institutional contexts. This systematic review examines the adoption and application of Web 2.0 tools in library websites globally, with a focus on trends, evaluation frameworks, barriers to usage, and strategic recommendations. For the study, a PRISMA-2020 guided review was conducted on 29 peer-reviewed articles published between 2010 and 2023. Databases searched for the study included Scopus, LISTA, and Google Scholar. Inclusion criteria required empirical studies focusing on Web 2.0 tools in library environments. It is found that social media platforms had been emerged as the most prevalent tool, followed by blogs, RSS feeds, and multimedia sharing. Content analysis was the dominant evaluation method, supplemented by surveys and mixed-method approaches. Key barriers included infrastructural limitations, digital literacy deficits, absence of formal policies, and low user engagement. In conclusion, Web 2.0 technologies have emerged as powerful catalysts in redefining library services, fostering enhanced interactivity, collaboration, and user-driven content creation. Libraries must transition from passive adoption to active integration of these tools, emphasizing participatory design principles that center user experience.